Asemeia ovata (Polygalaceae): Quantitative determination and evaluation in silico of identified substances by HPLC-DAD. (August 2018) - da Rocha, José Luiz Carneiro; da Silva, Danielle Figuerêdo; de Santana, Anne Ramos; da Costa, Diego Mota; Pastore, José Floriano Barêa; Alves, Clayton Queiroz; Santos Junior, Manoelito Coelho Santos; Brandão, Hugo Neves
Graphical abstract: Highlights: Identification and quantification using HPLC-DAD: rutin, luteolin-7- O -glucoside, caffeic acid, p -coumaric acid and trans -ferulic acid. Description of the interaction profiles of substances identified with respectives molecular targets. Description of potential compounds on hipercloridrose problems, hypoxia with various metabolic disorders, diabetes and breast cancer. Abstract: Background: In Brazil, the Asemeia genus has 19 species (12 endemic) and 2 varieties (both endemic) and some of them are found in semi-arid Bahia. Objective: The objective of this study was to quantitatively determine identified substances by HPLC-DAD in Asemeia ovata extracts and to predict their biological activities in silico . Method: The quantification method by HPLC-DAD has been validated according to the guidelines of the International Conference of Harmonization. The prediction in silico activities was made by Target Fishing methods (TF), followed by docking by the program DOCK 6.7 and assessment of interaction profiles for Protein-Ligand Interaction Profiler server. Results: It was possible to identify and quantify using HPLC-DAD substances: rutin, luteolin-7- O -glucoside, caffeic acid, p -coumaric acid and trans -ferulic acid. The ChemProt 2.0 server was selected for TF method, which has shown potential activity of compounds on molecular targets such as Carbonic anhydrase 12, epidermal growth factor receptor and sodium-glucose cotransporter 2. Conclusion: This work provides new results for the species both from a biological and chemical point of view, and has interesting potential to be discovered with the prospect of further studies.